Insular resting state functional connectivity is associated with gut microbiota diversity. (17th June 2019) - Curtis, Kaylah; Stewart, Christopher J.; Robinson, Meghan; Molfese, David L.; Gosnell, Savannah N.; Kosten, Thomas R.; Petrosino, Joseph F.; De La Garza, Richard; Salas, Ramiro
Abstract: The gut microbiota has recently gained attention as a possible modulator of brain activity. A number of reports suggest that the microbiota may be associated with neuropsychiatric conditions such as major depressive disorder, autism and anxiety. The gut microbiota is thought to influence the brain via vagus nerve signalling, among other possible mechanisms. The insula processes and integrates these vagal signals. To determine if microbiota diversity and structure modulate brain activity, we collected faecal samples and examined insular function using resting state functional connectivity (RSFC). Thirty healthy participants (non‐smokers, tobacco smokers and electronic cigarette users, n = 10 each) were studied. We found that the RSFC between the insula and several regions (frontal pole left, lateral occipital cortex right, lingual gyrus right and cerebellum 4, 5 and vermis 9) were associated with bacterial microbiota diversity and structure. In addition, two specific bacteria genera, Prevotella and Bacteroides, were specifically different in tobacco smokers and also associated with insular connectivity. In conclusion, we show that insular connectivity is associated with microbiome diversity, structure and at least two specific bateria genera. Furthemore, this association is potentially modulated by tobacco smoking, although the sample sizes for the different smoking groups were small and this result needs validation in a larger cohort. While replication is necessary, the microbiota is a readily accessible therapeutic target for modulating insular connectivity, which has previously been shown to be abnormal in anxiety and tobacco use disorders. Abstract : We show that tobacco smokers have gut bacteria different to non‐smokers and electronic cigarette users. The composition of gut bacteria (including bacteria prevalence specifically associated with tobacco smoking) correlates with the functional connectivity of the brain insula. The connectivity of the insula, especially with frontal regions, may be important in control of emotions and may be associated with drug abuse, making the microbiota a possible therapeutic target in psychiatry.